The Impact of Fear on Police Behavior and Public Safety - Cho, Sungwoo; Gonçalves, Felipe; Weisburst, Emily (The Review of Economics and Statistics, 2024)
Abstract We examine how changes in the salience of workplace risk affect police behavior and public safety. Specifically, we investigate cases of police officer deaths while on duty. Officers respond to a peer death by decreasing arrest activity for one to two months, consistent with heightened fear. Reductions are largest for low-level arrests and are more pronounced in smaller cities. Crime does not increase on average during this period, nor do we observe crime spikes in cities with larger or longer arrest declines. While shocks to perceived fatality risk generate substantial enforcement responses, officer fear is unlikely to harm public safety.